1983
DOI: 10.1128/aac.23.5.676
|View full text |Cite
|
Sign up to set email alerts
|

Anti-herpesvirus activity of the acyclic nucleoside 9-(1,3-dihydroxy-2-propoxymethyl)guanine

Abstract: The antiherpetic effects of a novel purine acyclic nucleoside, 9-(1,3-dihydroxy-2-propoxymethyl)guanine (DHPG), were compared with those of acyclovir in cell culture § and in mice. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
123
0
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(136 citation statements)
references
References 18 publications
11
123
0
2
Order By: Relevance
“…Our data confirm the potential of DHPG in the treatment of various other experimental HSV infections, including intravaginal infections in mice treated orally (23) and guinea pigs treated systemically (9), intraperitoneal and orofacial infections in mice treated systemically (5, 8), and intranasal infections of mice treated orally and systemically (6). DHPG is active whether given orally, by s.c. or intraperitoneal injection, or, as shown in our experiments, by topical application at the inoculation site.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Our data confirm the potential of DHPG in the treatment of various other experimental HSV infections, including intravaginal infections in mice treated orally (23) and guinea pigs treated systemically (9), intraperitoneal and orofacial infections in mice treated systemically (5, 8), and intranasal infections of mice treated orally and systemically (6). DHPG is active whether given orally, by s.c. or intraperitoneal injection, or, as shown in our experiments, by topical application at the inoculation site.…”
supporting
confidence: 67%
“…The clearance of infectious virus from ganglia during the acute phase of infection was followed by early establishment of latency. 9-(1,3-Dihydroxy-2-propoxymethyl)guanine (0.03 ,ug/ml) significantly inhibited the synthesis of infectious virus in explant cultures of latently infected ganglia, and at concentrations higher than 8 ,Lg/ml no infectious virus was detectable in ganglia explant cultures.The acyclic nucleoside 9-(1,3-dihydroxy-2-propoxymethyl)guanine (DHPG), synthesized by the procedures described by Ogilvie and Gillian (20), Martin et al (19a), and Ashton et al (1) has been shown to be an effective inhibitor of herpes simplex virus (HSV) and cytomegalovirus replication in cell cultures (1, 2, 4, 5,19,23,26). DHPG proved to be superior to acyclovir (ACV) in the treatment of HSV-induced encephalitis and vaginitis in mice (1, 5, 6, 8,26) and was effective in reducing the severity of primary and recrudescent lesions induced by genital infection of guinea pigs (9) and by eye infections in rabbits (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports in which HSV-infected cells phosphorylated GCV more favorably than ACV when evaluated by kinase activities. 6,8,10 A total of 200 ng of ponicidin per mL, for example, enhanced the cytotoxicity of GCV against HSV-TK gene-transfected COS-1 cells by at least 20-fold. This means that less than one-twentieth the therapeutic dose of GCV in combination with ponicidin may produce the same efficacy as its therapeutic dose in cancer gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to be 26 times more potent than acyclovir against HCMV in vitro ( Morse et al, 1993). Previous studies reported excellent in vitro activity of GCV against human herpes virus type 6, human herpes simplex viruses types 1 and 2, varicella-zoster virus, and Epstein-Barr virus (Smee et al, 1983;Andrei et al, 1991;Shigeta et al, 1991;Snoeck et al, 1991;Konno et al, 1993). It was approved for the induction and maintenance therapy of HCMV retinitis in AIDS patients in 1989 and has been widely used.…”
mentioning
confidence: 99%